2016
DOI: 10.1038/jp.2016.202
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of short-term variation and the impact of multiple recordings on measurement accuracy

Abstract: Single pathological STV values should be corroborated by further measurements in a 24-h interval in otherwise low-risk fetuses before inducing delivery. This may help to avoid unnecessary early births and give the fetus valuable days for intrauterine maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…There is growing interest in using CFM to interpret features of the fECG to either detect cardiac rhythm abnormalities or identify fetal compromise . Given that CFM can record the fECG with adequate quality for interpretation in a large number of cases, the interest in this methodology is likely to increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing interest in using CFM to interpret features of the fECG to either detect cardiac rhythm abnormalities or identify fetal compromise . Given that CFM can record the fECG with adequate quality for interpretation in a large number of cases, the interest in this methodology is likely to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, prognostic accuracy studies of CFM should be performed where the recording is not revealed, so that fECG features can be accurately correlated to fetal outcome. One such study found that a single episode of STV <4 ms had a positive predictive value for fetal compromise of 39%, which rose to 80% if there were three episodes of STV < 4 ms . In addition, studies of CFM should focus on populations most likely to benefit such as women with suspected fetal compromise (eg, small‐for‐gestational‐age infants and reduced fetal movements).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of different mechanisms may cause acidemia in a fetus and the present study was not designed to determine the exact cause of acidemia. Nevertheless, the different causes of acidemia may include autonomic system dysregulation such as vagal excitability (which often leads to fetal distress and neonatal asphyxia), any disruption of the adrenergic system versus cholinergic system balance, fetal movement, fetal age, and gestational complications that affect placenta/fetus blood and gas exchange (such as preeclampsia, thrombotic diseases, gestational diabetes, oligohydramnios, abnormal torsion and twining of the umbilical cord, abnormal placental position, or placental abruption), eventually resulting in hypoxemia, hypercapnia, and metabolic acidosis [ 38 , 50 55 ]. A recent study using an in vivo sheep model also found that increasing values of AC/DC suggested that activation of the fetal autonomic nervous system as the time evolution of AC/DC correlated well with the acid-base balance [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the ultrasound-based CTG monitors, although the fetal ECG monitor (Monica AN24) uses different signals to acquire FHR data, the monitor relies on the same averaging algorithm as introduced by Dawes and Redman [ 16 ] to calculate STV and other automated FHR parameters. In all cases, FHR data selected for the analysis fulfilled the Dawes Redman criteria.…”
Section: Methodsmentioning
confidence: 99%